Student Anxiety Level When Going to College in the Mathematics Education Study Program with Mathematics Scores - Santoso, Fransiskus Gatot; Ariyanti, Gregoria (Mosharafa: Jurnal Pendidikan Matematika, 2023)
Tujuan dari penelitian ini adalah untuk mengetahui gambaran tingkat kecemasan pada mahasiswa Program Studi Pendidikan Matematika (PSPM) UKWMS ketika akan berkuliah di PSPM terhadap nilai matematika di STTB SMA/SMK. Jenis penelitian ini ialah penelitian deskriptif. Subjek penelitian adalah mahasiswa PSPM (Kampus Kota Madiun) UKWMS Angkatan Tahun 2022 sebanyak 7 mahasiswa. Metode pengumpulan data yang digunakan dalam penelitian ini ialah metode kuesioner. Kuesioner yang dibuat adalah kecemasan mahasiswa dalam menghadapi mata pelajaran matematika. Aspek kecemasan yang diteliti adalah aspek fisik, aspek mental, dan aspek perilaku. Metode analisis data dalam penelitian ini ialah statistik deskriptif karena data berupa angka-angka. Data ini berupa skor kecemasan mahasiswa dan nilai matematika di STTB SMA/SMK mahasiswa. Hasil penelitian ini diperoleh rataan skor kecemasan mahasiswa ketika akan berkuliah di PSPM berdasarkan aspek fisik sebesar 42,43 (kriteria tingkat kecemasan sedang), aspek mental sebesar 42,29 (kriteria tingkat kecemasan sedang), dan aspek perilaku sebesar 39,43 (kriteria tingkat kecemasan rendah). Secara keseluruhan rataan skor kecemasan mahasiswa ketika akan berkuliah di PSPM sebesar 124,14 (kriteria tingkat kecemasan sedang). Sedangkan rataan nilai matematika mahasiswa di STTB SMA/SMK sebesar 84,91. The purpose of this study is to determine the level of anxiety in students of the UKWMS Mathematics Education Study Program (PSPM) when going to study at PSPM mathematics grades in the high school/vocational school STTB. This type of research is descriptive. The research subjects were 7 MESP (Madiun City Campus) WMSCU Class of 2022 students. The data collection method used in this research is the questionnaire method. The questionnaire made is about student anxiety in facing math subjects. The aspects of anxiety studied are physical, mental, and behavioral. The data analysis method in this research is descriptive statistics because the data is in the form of numbers. This data is in the form of student anxiety scores and math scores in the STTB SMA / SMK students. The results of this study obtained an average student anxiety score when going to college at PSPM based on physical aspects of 42.43 (moderate anxiety level criteria), mental aspects of 42.29 (moderate anxiety level criteria), and behavioral aspects of 39.43 (low anxiety level criteria). Overall, the average score of student anxiety when studying at PSPM is 124.14 (moderate anxiety level criteria). Meanwhile, the average student's mathematics score at the high /vocational school STTB is 84.91.